2013
DOI: 10.3344/kjp.2013.26.4.356
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Urinary Trypsin Inhibitor Against Neuropathic Pain in Rat Models

Abstract: BackgroundNerve injury sometimes leads to chronic neuropathic pain associated with neuroinflammation in the nervous system. In the case of chronic neuropathic pain, the inflammatory and algesic mediators become predominant and result in pain hypersensitivity following nervous system damage. It is well known that urinary trypsin inhibitor (ulinastatin, UTI) has an anti-inflammatory activity. Recently, the neuroprotective action of UTI on the nervous system after ischemic injury has been reported. Thus, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…First, only one dose of UTI (50,000 U/kg intravenously) was used in the present study. We used the dosage of UTI which was effective in the previous study which was conducted as a preliminary study [12]. However, another study on the effect of UTI on the inflammatory response demonstrated the inhibition of TNF-␣ production with a higher dosage [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, only one dose of UTI (50,000 U/kg intravenously) was used in the present study. We used the dosage of UTI which was effective in the previous study which was conducted as a preliminary study [12]. However, another study on the effect of UTI on the inflammatory response demonstrated the inhibition of TNF-␣ production with a higher dosage [23].…”
Section: Discussionmentioning
confidence: 99%
“…The rats in group U pre were administered 50,000 U/kg of UTI (Ulistin ® , Hanlim Pharmaceutical Co. Ltd., Seoul, Korea) through the tail vein for three days immediately following the SNL procedure, before the development of neuropathic pain was confirmed. The rats in group U post were administered 50,000 U/kg of UTI through the tail vein for three days from the 3rd day following the SNL procedure, after the development of neuropathic pain was confirmed [12].…”
Section: Groups and Drug Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of neuroinflammation, serine protease inhibitor has inhibitory properties on the proinflammatory cytokines and has the effect of attenuating the development of neuropathic pain [2,14]. Gabexate mesilate is one of those serine protease inhibitors with properties of antiinflammation and TNF-α inhibition by the suppression of NF-κB and the NO pathway [13,15,17] which are closely related with an inflammatory response and the development of neuropathic pain after spinal nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…Its property of TNF-α inhibition via monocyte also provides effectiveness in the treatment of sepsis-associated disseminated intravascular coagulation [13]. Recent studies have shown that the inhibitory effects of serine protease inhibitor on the proinflammatory cytokines can attenuate the development of neuropathic pain [2,14]. Gabexate mesilate also showed a protective effect after spinal cord trauma by inhibition of the increase in the myeloperoxidase activity in an animal model [15].…”
mentioning
confidence: 99%